PENGELOLAAN KEUANGAN DESA DALAM MEWUJUDKAN GOOD GOVERNANCE - Anifah, Anifah; Heriyanto, Meyzi; Muchid, Muchid (Jurnal Ilmu Administrasi Negara, 2018)
Management of Village Finance in Achieving Good Governance. This study aims to analyze the management of village finances in realizing good governance in the Village of Tanjung Medan Tambusai North District Rokan Hulu District. The research informant is the Village Head, Secretary and Treasurer. Key informant is 2 people Village Consultative Board. Data collection techniques used documentation and library techniques. Data analysis technique used is interactive model with data reduction measures, data display, decision making and verification. The result of this research can be concluded that the process of village financial management in Tanjung Medan Village Tambusai Utara District Rokan Hulu Regency has not been implemented optimally although it has implemented every stages of village financial management. Inhibiting factors affecting village financial management are the factors of funding and human resources and the lack of participation of the villagers of Tanjung Medan village in overseeing the village financial management represented by BPD.